Solid oxide battery containing gradient layer and preparation method

By introducing a gradient layer into the solid oxide battery, the problem of insufficient chemical stability of the proton conductor framework at high temperatures is solved, and the long-term stable operation of the battery and the adaptability of multiple fuels is achieved.

CN119542479AActive Publication Date: 2025-02-28NORTH CHINA ELECTRIC POWER UNIV
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411578845.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-28
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The proton conductor skeleton contains Ba elements, which will decompose under the action of moisture pressure and CO2, resulting in severe performance decay of solid oxide fuel cells during long-term operation.

Method used

The solid oxide battery design with a gradient layer is adopted. By optimizing the electrolyte material and electrode structure, chemical stability is enhanced, and a barrier layer and gradient layer are provided in the protective layer. The gradient layer is generated by reacting with the proton conductor skeleton to coordinate interface stress and internal stress.

Benefits of technology

It significantly improves the chemical stability of solid oxide batteries at high temperatures, extends the service life of the batteries, and enables them to adapt to a variety of fuels, improving application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542479A_ABST
    Figure CN119542479A_ABST
Patent Text Reader

Abstract

The invention provides a solid oxide cell containing a gradient layer and a preparation method, and belongs to the technical field of solid oxide fuel cells, and a functional layer of the solid oxide cell comprises a proton conductor skeleton, a protective layer and a catalyst layer; the protective layer is attached to the surface of the proton conductor framework and comprises a barrier layer and a gradient layer, and the gradient layer is generated through reaction between the protective layer and the proton conductor framework close to the protective layer; the catalyst layer is attached to the barrier layer. By optimizing the electrolyte material and the electrode structure, the chemical stability of the solid oxide battery at a high temperature is enhanced, in addition, the solid oxide battery is more flexible in fuel selection, various fuels such as hydrogen and natural gas can be used, and fuel preparation through water electrolysis and co-electrolysis can be realized, so that the application prospect of the solid oxide battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid oxide fuel cells, and in particular relates to a solid oxide fuel cell containing a gradient layer and a preparation method thereof. Background Art

[0002] Solid oxide fuel cell (SOFC) is a clean energy conversion device that can directly convert chemical energy into electrical energy. It can generate electricity in fuel cell mode or prepare fuel in electrolysis mode. According to the different ions conducted by the electrolyte material, SOFC can be divided into oxygen ion conductor type (O-SOFC) and proton conductor type (H-SOFC). Traditional high-temperature O-SOFC has been developed for many years, with mature preparation technology and excellent performance at high temperature. However, as the working conditions of the battery develop towards medium and low temperatures, proton conductor SOFC (H-SOFC) has received widespread attention due to its lower operating temperature, smaller activation energy value and higher battery efficiency. However, H-SOFC is not yet mature, and the chemical stability and mechanical stability of proton conductor materials at high temperatures still need to be further improved to ensure that they do not degrade during long-term operation.

[0003] The key technical problem limiting H-SOFC is that the proton conductor skeleton contains Ba elements, which will decompose under the action of water pressure and CO2, resulting in serious performance degradation during long-term operation of the battery. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a solid oxide battery containing a gradient layer and a preparation method thereof. By optimizing the electrolyte material and electrode structure, its chemical stability at high temperature is enhanced. In addition, this solid oxide battery is more flexible in fuel selection, and can use a variety of fuels such as hydrogen and natural gas, and can be used for water electrolysis and co-electrolysis, thereby further improving its application prospects.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] On the one hand, the present invention provides a solid oxide battery, the functional layer of which includes a proton conductor skeleton, a protective layer and a catalyst layer; the protective layer is attached to the surface of the proton conductor skeleton, and includes a barrier layer and a gradient layer, and the gradient layer is generated by the reaction of the protective layer with the proton conductor skeleton in proximity; the catalyst layer is attached to the barrier layer.

[0007] Furthermore, the thickness of the gradient layer in the solid oxide battery is 1.0-4.5 μm.

[0008] Furthermore, the material of the proton conductor skeleton includes: BaZr 1-x Y x O3-δ 、BaZr 1-x Yb x O 3-δ 、BaZr 1-x- y Ce y Y x O 3-δ 、BaZr 1-x-y-z Ce z Y y Yb x O 3-δ One or more of, where 0 <x<1,0<y<1,0<z<1,0<δ<1。

[0009] Furthermore, the material of the protective layer includes: CeO2, Ce 1-x G x O 2-δ 、Ce 1-x La x O 2-δ 、Sm 1-x Ce x O 2-δ One or more of, where 0 <x<1,0<y<1,0<δ<1。

[0010] Furthermore, the porosity of the solid oxide battery functional layer is 10%-60%.

[0011] In another aspect, the present invention discloses a method for preparing the above-mentioned solid oxide battery, comprising:

[0012] A proton conductor skeleton of a functional layer is prepared; a protective layer is prepared on the surface of the proton conductor skeleton; and a catalyst layer is prepared on the surface of the protective layer.

[0013] Furthermore, preparing a protective layer on the surface of the proton conductor skeleton includes: dissolving the material of the protective layer in an organic solvent and stirring to prepare an impregnation solution; dripping the impregnation solution onto the proton conductor skeleton by an impregnation method, then performing a heat preservation treatment at a first preset temperature, cooling after the heat preservation is completed, repeating the impregnation process until the impregnation mass no longer increases, and then performing a sintering.

[0014] Furthermore, the particle size of the material powder of the protective layer is not greater than 60 nm, and the concentration of the impregnation solution is 0.5-3.0 mol / L.

[0015] Furthermore, the first preset temperature is 300-500° C. and kept at this temperature for 1-5 hours; the primary sintering process is: heating to 1100-1500° C. at a rate of no more than 5° C. / min and kept at this temperature for 4-10 hours, and then cooling to room temperature.

[0016] Furthermore, preparing a catalyst layer on the surface of the protective layer includes: preparing a catalyst material on the surface of the protective layer, followed by secondary sintering, wherein the secondary sintering process is: heating to 600-1100°C at a rate not greater than 3°C / min, maintaining for 2-20h, and then cooling to room temperature.

[0017] Compared with the prior art, the technical solution provided by the present invention brings the following beneficial effects: There are methods for preparing protective layers in the prior art, such as hydrothermal reaction, but there are corresponding problems. For example, the hydrothermal method is easier to implement in preparing protective layers in roughly planar or relatively large holes, and the protective effect is better. When the hole size is relatively small, the thickness of the protective layer inside the hole is uneven and the protective effect is poor due to factors such as the hydrothermal reaction kinetics. In addition, due to the difference in physical properties between the protective layer and the conductor skeleton material, the interface tends to split during use. In the present application, the protective layer is set to two layers, including a barrier layer and a gradient layer. The gradient layer The protective layer is generated by the reaction with the proton conductor skeleton, and the gradient layer can coordinate the internal stress and interface stress caused by the different physical properties between the barrier layer and the surface of the proton conductor skeleton; secondly, due to the provision of the gradient layer, the thickness of the barrier layer can be appropriately set to be thicker to avoid local areas not being completely covered by the protective layer; finally, due to the existence of the barrier layer and the preparation method of the protective layer of the present application, it is ensured that the barrier layer can completely cover the proton conductor skeleton, realize the transfer of the active interface of the electrochemical reaction, and transfer from the catalyst-proton skeleton-gas three-phase interface to the catalyst-barrier layer-gas interface, thereby reducing the reaction between the proton conductor skeleton and various adsorbed species. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 A schematic diagram of the structure of a solid oxide battery provided by an embodiment of the present invention;

[0020] Figure 2 The SEM image and elemental energy spectrum of the solid oxide half-cell provided in Example 1 of the present invention.

[0021] Figure numerals: 1. proton conductor skeleton; 2. protective layer; 3. oxygen electrode catalyst layer; 4. fuel electrode catalyst layer. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The specific implementation of the present invention is not limited to the specific embodiments given here, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the disclosed specific embodiments.

[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and do not limit the present invention.

[0024] The embodiment of the present invention discloses a solid oxide battery, such as Figure 1 As shown, the functional layer of the solid oxide battery includes a proton conductor skeleton 1, a protective layer 2 and a catalyst layer; the protective layer 2 is attached to the surface of the proton conductor skeleton 1, and includes a barrier layer and a gradient layer (the barrier layer and the gradient layer are relatively thin and are not shown in the figure), and the gradient layer is generated by the reaction of the protective layer 2 with the proton conductor skeleton 1 close to it; the catalyst layer is attached to the barrier layer, and the catalyst layer includes an oxygen electrode catalyst layer 3 and a fuel electrode catalyst layer 4, Figure 1 The proton conductor skeleton 1 and the electrolyte layer shown in the figure are made of the same material, that is, the oxygen electrode, the fuel electrode and the electrolyte are made of the same proton conductor material, which is a preferred structure. The integrated overall structure ensures the close combination of the electrode and the electrolyte layer, effectively avoiding the problem of interface cracks that may occur during operation, and enhancing the stability and durability of the battery.

[0025] It is understandable that the proton conductor skeleton can also be made of different materials, such as BZY for the oxygen electrode and BZCY for the fuel electrode. The electrolyte layer can also be the same as or different from the material of the oxygen electrode or the fuel electrode in the proton conductor skeleton.

[0026] There are methods for preparing protective layers in the prior art, such as hydrothermal reaction, but there are corresponding problems. For example, the hydrothermal method is easy to implement in preparing protective layers in roughly planar or relatively large holes, and the protective effect is better. When the hole size is relatively small, the thickness of the internal protective layer is uneven and the protective effect is poor due to factors such as hydrothermal reaction kinetics. In addition, since the protective layer and the conductor skeleton have different physical properties due to different materials, the interface tends to split during use. In this application, the protective layer is set as two layers, including a barrier layer and a gradient layer. The gradient layer is generated by the reaction of the protective layer and the proton conductor skeleton. The gradient layer can coordinate the internal stress and interface stress caused by the different physical properties between the barrier layer and the surface of the proton conductor skeleton; secondly, due to the presence of the gradient layer, the thickness of the barrier layer can be appropriately set to be thicker to avoid local areas not being completely covered by the protective layer; finally, due to the existence of the barrier layer and the preparation method of the protective layer of the present application, it is ensured that the barrier layer can completely cover the proton conductor skeleton, realize the transfer of the active interface of the electrochemical reaction, and transfer from the catalyst-proton skeleton-gas three-phase interface to the catalyst-barrier layer-gas interface, thereby reducing the reaction between the proton conductor skeleton and various adsorbed species.

[0027] Specifically, the thickness of the gradient layer in the solid oxide battery is 1.0-4.5 μm. On the one hand, the smaller thickness of the gradient layer affects the coordination between the protective layer and the proton conductor skeleton. On the other hand, if the thickness of the gradient layer is larger, it affects the thickness of the barrier layer, that is, if the total thickness of the protective layer is certain, the gradient layer is too thick, and the barrier layer is thinner. If the barrier layer is too thin, the life of the solid oxide battery will be shortened. Setting the thickness of the gradient layer to 1.0-4.5 μm can solve the above two technical problems. It should be pointed out that the thickness of the gradient layer of the present invention is obtained by measuring the thickness of at least 5 positions and taking the average value.

[0028] Specifically, the materials of the proton conductor skeleton include: CeO2, BaZr 1-x Y x O 3-δ 、BaZr 1-x Yb x O 3-δ 、BaZr 1-x-y Ce y Y x O 3-δ 、BaZr 1-x-y-z Ce z Y y Yb x O 3-δ One or more of, where 0 <x<1,0<y<1,0<z<1,0<δ<1。

[0029] Specifically, the material of the protective layer includes: Ce 1-x G x O2-δ ,La 1-x G x O 2-δ 、Sm 1-x G x O 2-δ One or more of, where 0 <x<1,0<y<1,0<δ<1。

[0030] Specifically, the porosity of the solid oxide battery functional layer is 10%-60%.

[0031] The present invention also provides a method for preparing the above-mentioned solid oxide battery, comprising:

[0032] S1 prepares the proton conductor skeleton of the functional layer.

[0033] In the proton conductor skeleton, the oxygen electrode, the fuel electrode and the electrolyte may be made of the same material or different materials. When the same material is used, since the same materials have the same thermal properties, they have higher stability during heating and cooling and during operation. In the embodiment of the present invention, the oxygen electrode, the fuel electrode and the electrolyte are all made of the same material.

[0034] The preparation of the proton conductor skeleton includes: a) preparing a three-layer structure including a proton conductor porous skeleton layer on the oxygen electrode side containing a pore-forming agent, a proton conductor dense electrolyte layer, and a proton conductor porous skeleton layer on the fuel electrode side containing a pore-forming agent, and the preparation steps of each layer include but are not limited to: one or more of: tape casting, screen printing, spin coating, spraying, and vapor deposition; b) high-temperature calcining the three-layer structure to obtain an integrated "porous layer|dense layer|porous layer" structure with proton conduction.

[0035] Specifically, the preparation steps include:

[0036] S10: Proton conductor powder and pore former powder are mixed in a mass ratio of 6:(3-5), dispersant, plasticizer and binder are added to prepare oxygen electrode and fuel electrode side skeleton casting slurry, and appropriate amount of zirconium oxide ball milling beads are added to carry out ball milling for 36 hours to ensure mixing uniformity.

[0037] S11: Add dispersant, plasticizer and binder to proton conductor powder to prepare oxygen electrode side skeleton casting slurry, add appropriate amount of zirconium oxide ball milling beads and ball mill for 36 hours to ensure mixing uniformity.

[0038] S12: The oxygen electrode, the fuel electrode and the electrolyte slurry are prepared by using a membrane belt casting machine to obtain electrode and electrolyte casting membrane sheets.

[0039] S13 stacks the three layers of cast membrane according to electrode cast membrane | electrolyte cast membrane | electrode cast membrane, and then hot presses them in multiple steps at 50-85°C and 10-60Mpa pressure, and obtains an integrated "porous layer | dense layer | porous layer" structural skeleton with proton conduction after sintering. Multi-step hot pressing refers to hot pressing after stacking the electrode cast membrane on one side and the electrolyte cast membrane, and then hot pressing the electrode cast membrane on the other side and the semi-finished product pressed in the previous step.

[0040] The sintering is carried out in an oxidizing atmosphere, placing the integrated proton conductor skeleton green body containing the pore-forming agent in a muffle furnace, first performing a binder removal treatment, and then heating to 1300-1450° C. and sintering for 8-10 hours to obtain the integrated proton conductor skeleton.

[0041] Preferably, the porosity of the prepared integrated proton conductor skeleton is 10-60%, and the average pore size is 10-100 μm.

[0042] S2 prepares a protective layer on the surface of the proton conductor skeleton. It includes:

[0043] S20: dissolving the material of the protective layer in an organic solvent and stirring to prepare an impregnation solution; specifically, dissolving the protective layer material powder in an ethanol solution, adding a proper amount of a dispersant and a surfactant, and preparing a protective layer material impregnation solution with a concentration of 0.5-3.0 mol / L.

[0044] Preferably, the protective layer nano powder particles are no larger than 60 nm, the organic solvent includes but is not limited to ethanol, acetone, etc., the dispersant is triethanolamine (TEA), and the surfactant is polyether (P123).

[0045] S21 uses an impregnation method to drop the impregnation solution onto the proton conductor skeleton, and then performs a heat preservation treatment at a first preset temperature. After the heat preservation is completed, the temperature is lowered and the impregnation process is repeated until the impregnation mass no longer increases, and then sintering is performed once.

[0046] The impregnation solution is dripped into the integrated proton conductor skeleton, and the skeleton is placed in a muffle furnace for heat preservation at high temperature. The above operation is repeated multiple times until the solution can no longer penetrate.

[0047] The protective layer nano powder is dissolved in an organic solvent, a dispersant and a surfactant are added, and an appropriate amount of zirconium oxide ball milling beads are added for ball milling for 36 hours to ensure mixing uniformity; the impregnation solution is dripped on the integrated proton conductor skeleton, and the impregnation solution is placed in a furnace for high-temperature treatment. The high-temperature treatment process is: the temperature is raised to 300-500°C at a temperature of no more than 10°C / min, and the temperature is kept for 1-5 hours, and then the temperature is cooled to room temperature at a temperature of no more than 10°C / min; the impregnation steps are repeated many times until the impregnation mass no longer increases, and then sintering is performed once. The present invention prepares a protective layer on the surface of the integrated proton conductor skeleton by impregnation, and the control difficulty of this application is relatively low. The reason is that the impregnation is carried out until the impregnation mass no longer increases, and the problem of controlling the number of impregnations does not need to be considered. After the impregnation is completed, the temperature is maintained at 300-500°C for a certain period of time. This time is the debinding process, and no sintering is performed, that is, the protective layer is only physically attached to the integrated proton conductor skeleton, and no high-temperature diffusion and reaction are performed.

[0048] The primary sintering process is: heating to 1100-1500°C at a rate of no more than 5°C / min, keeping the temperature for 4-10h, and then cooling to room temperature. Furthermore, the temperature is cooled to room temperature at a rate of no more than 5°C / min during the cooling process. The purpose of the primary sintering process is to promote the sintering and forming of the protective layer after debinding and increase its density on the one hand, and on the other hand, part of the protective layer reacts with the proton conductor skeleton to generate a gradient layer for coordinating the difference in thermophysical properties between the barrier layer and the proton conductor skeleton to improve the interface coordination deformation ability between the two. Secondly, the heating temperature and the holding time are also very important. Since secondary sintering is required for the subsequent preparation of solid oxide battery blanks, high-temperature sintering will affect the thickness of the gradient layer, and the first sintering needs to satisfy the requirement of sintering the unreacted protective layer to be dense, so that the thickness of the barrier layer is 200-500nm. The present application controls the sintering temperature and the holding time, which not only ensures that part of the protective layer reacts with the proton conductor skeleton to generate a gradient layer, but also can sinter the unreacted protective layer to be dense, and combined with the subsequent secondary sintering, the thickness of the prepared gradient layer is 1.0-4.5μm.

[0049] S3: preparing a catalyst layer on the surface of the protective layer.

[0050] In the embodiment of the present invention, the oxygen electrode catalyst layer is composed of an electronic conductor or a mixed ion and electronic conductor, and the specific materials include but are not limited to: Pr6O 11 、Ce 1-x Pr x O2、PrNi 1-x Co x O 3-δ (PNC), Ba 1-x Sr x Co y Fe 1-y O 3-δ (BSCF), La1-x Sr x Co y Fe 1-y O 3-δ (LSCF), BaCo y Fe 1-x-y-z Zr x Y z O 3-δ (BCFZY), where 0 < x < 1, 0 < y < 1, 0 < z < 1, 0 < δ < 1. The fuel electrode catalyst is composed of a metal or cermet composite material or an electron-ion mixed conductor. Specific materials include, but are not limited to: Ni, NiFe, Ni / Ce 1-x Gd x O 2-δ and Sr2Fe 2-x Mo x O 6-δ (SFM), where 0 < x < 1, 0 < y < 1, 0 < δ < 1.

[0051] Prepare the catalyst material on the surface of the protective layer, and then perform secondary sintering. The secondary sintering process is as follows: heat up to 600 - 1100°C at a rate not exceeding 3°C / min and hold for 2 - 20 h, and then cool down to room temperature. Specifically, the sintering process of the present invention is: heat up to 650 - 700°C at a rate not exceeding 1°C / min and hold for at least 30 min, heat up to 600 - 1100°C at a rate not exceeding 3°C / min and hold for 2 - 20 h, and then cool down to room temperature at a rate not exceeding 5°C / min. On the one hand, this sintering temperature and holding time are beneficial to sinter the catalyst material attached to the surface of the protective layer into a catalyst layer. On the other hand, this sintering temperature and holding time will affect the formation thickness of the gradient layer, so that the thickness of the finally prepared gradient layer is 1.0 - 4.5 μm.

[0052] Preferably, in the embodiments of the present invention, the oxygen electrode and fuel electrode materials are attached to the barrier layer by an impregnation method, and then prepared by secondary sintering.

[0053] To further illustrate the present invention, the technical solutions provided by the present invention will be described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0054] Example 1

[0055] The embodiments of the present invention provide a method for preparing a solid oxide battery and a solid oxide battery prepared by using this method. The method includes:

[0056] S1 Prepare the proton conductor framework of the functional layer.

[0057] Use BaZr 0.7Ce 0.2 Y 0.1 O 3-δ As an integrated proton conductor skeleton, specifically, the powder and the pore-forming agent powder are mixed in a mass ratio of 6:4, a dispersant, a plasticizer and a binder are added to prepare an electrode side skeleton casting slurry, and an appropriate amount of zirconium oxide ball milling beads are added for ball milling for 36 hours to ensure mixing uniformity. 0.7 Ce 0.2 Y 0.1 O 3-δ The powder is used to prepare the electrolyte casting slurry. The electrode and electrolyte slurry are used to prepare the electrode and electrolyte casting membrane using a membrane belt casting machine. The three layers of casting membrane are stacked according to the electrode casting membrane|electrolyte casting membrane|electrode casting membrane, and then multi-step hot pressing is performed at 50°C and 10Mpa pressure. After sintering, an integrated "porous layer|dense layer|porous layer" structural skeleton with proton conduction is obtained, and the sintering temperature is kept at 1400°C for 10 hours. The porosity of the prepared BZCY conductor skeleton is 10%, and the average pore size is 10μm.

[0058] S2: preparing a protective layer on the surface of the proton conductor skeleton.

[0059] GDC powder (molar composition of 40% Gd2O3 stabilized CeO2) was dissolved in ethanol solution, and appropriate amount of dispersant and surfactant were added to prepare GDC impregnation solution with concentration of 0.5 mol / L. The impregnation solution was dripped into the BZCY conductor skeleton, and placed in a muffle furnace for heat preservation at high temperature. The above operation was repeated many times until the solution could not penetrate, and then kept at 1100℃ for 4 hours, and then cooled to room temperature.

[0060] S3: preparing a catalyst layer on the surface of the protective layer.

[0061] According to the molar ratio of Pr:Ni:Co=2:1:1, metal nitrates Pr(NO3)3, Ni(NO3)3, and Co(NO3)2 were mixed, and then a surfactant was added at 10% of the total mass of the added Pr, Ni, and Co elements, and a certain amount of water was added to prepare a PNC oxygen electrode impregnation solution with a concentration of 0.7 mol / L.

[0062] The metal nitrate solutions were mixed according to the molar ratio of Ni:Sm:Ce=5:1:4, and then a surfactant was added according to 10% of the total mass of Ni, Sm, and Ce elements, and a certain amount of water was added to prepare a Ni / SDC fuel electrode impregnation solution with a concentration of 0.7 mol / L.

[0063] The above impregnation solution is absorbed and dripped into the electrode skeleton of the corresponding functional area respectively, and then placed in a muffle furnace for debinding treatment. The above operation is repeated many times until the solution can no longer penetrate, and finally a secondary sintering is performed to obtain a complete solid oxide battery. The secondary sintering process is: keep warm at 600°C for 2h, and finally cool to room temperature.

[0064] The morphology of the prepared solid oxide battery was observed by SEM. Figure 2 As shown, it can be seen that the protective layer completely covers the proton conductor skeleton, the thickness of the prepared gradient layer is 1.0 μm, and from the elemental spectrum it can be seen that the gradient layer is a Y and Ba intermediate phase.

[0065] The prepared solid oxide battery operated at 500°C for 1000 h without any power density decay.

[0066] Example 2

[0067] An embodiment of the present invention provides a method for preparing a solid oxide battery, and a solid oxide battery prepared by the method, the method comprising:

[0068] S1 prepares the proton conductor skeleton of the functional layer.

[0069] Using BaZr 0.7 Ce 0.2 Y 0.1 O 3-δ As an integrated proton conductor skeleton, specifically, the powder and the pore-forming agent powder are mixed in a mass ratio of 6:4, a dispersant, a plasticizer and a binder are added to prepare an electrode side skeleton casting slurry, and an appropriate amount of zirconium oxide ball milling beads are added for ball milling for 36 hours to ensure mixing uniformity. 0.7 Ce 0.2 Y 0.1 O 3-δ The powder is used to prepare the electrolyte casting slurry, and the electrode and electrolyte slurry are used to prepare the electrode and electrolyte casting membrane using a membrane belt casting machine. The three layers of casting membrane are stacked according to the electrode casting membrane|electrolyte casting membrane|electrode casting membrane, and then multi-step hot pressing is performed at 60°C and 30Mpa pressure. After sintering, an integrated "porous layer|dense layer|porous layer" structural skeleton with proton conduction is obtained, and the sintering temperature is kept at 1400°C for 10 hours. The porosity of the prepared BZCY conductor skeleton is 30%, and the average pore size is 35μm.

[0070] S2: preparing a protective layer on the surface of the proton conductor skeleton.

[0071] GDC powder (molar composition of 40% Gd2O3 stabilized CeO2) was dissolved in an ethanol solution, and appropriate amounts of dispersants and surfactants were added to prepare a GDC impregnation solution with a concentration of 1.5 mol / L. The impregnation solution was dripped into the BZCY conductor skeleton, placed in a muffle furnace for heat preservation at high temperature, and the above operation was repeated many times until the solution could no longer penetrate, and then kept at 1250℃ for 5 hours, and then cooled to room temperature.

[0072] S3: preparing a catalyst layer on the surface of the protective layer.

[0073] According to the molar ratio of Pr:Ni:Co=2:1:1, metal nitrates Pr(NO3)3, Ni(NO3)3, and Co(NO3)2 were mixed, and then a surfactant was added at 10% of the total mass of the added Pr, Ni, and Co elements, and a certain amount of water was added to prepare a PNC oxygen electrode impregnation solution with a concentration of 0.7 mol / L.

[0074] The metal nitrate solutions were mixed according to the molar ratio of Ni:Sm:Ce=5:1:4, and then a surfactant was added according to 10% of the total mass of Ni, Sm, and Ce elements, and a certain amount of water was added to prepare a Ni / SDC fuel electrode impregnation solution with a concentration of 0.7 mol / L.

[0075] The above impregnation solution is absorbed and dripped into the electrode skeleton of the corresponding functional area respectively, and then placed in a muffle furnace for debinding treatment. The above operation is repeated many times until the solution can no longer penetrate, and finally a secondary sintering is performed to obtain a complete solid oxide battery. The secondary sintering process is: keep warm at 800°C for 2h, and finally cool to room temperature.

[0076] The prepared solid oxide battery protection layer completely covers the proton conductor skeleton, the prepared gradient layer has a thickness of 2 μm, and the gradient layer is a Y and Ba intermediate phase.

[0077] The prepared solid oxide battery operated at 500°C for 1000 h without any power density decay.

[0078] Example 3

[0079] An embodiment of the present invention provides a method for preparing a solid oxide battery, and a solid oxide battery prepared by the method, the method comprising:

[0080] S1 prepares the proton conductor skeleton of the functional layer.

[0081] Using BaZr 0.7 Ce 0.2 Y 0.1 O 3-δAs an integrated proton conductor skeleton, specifically, the powder and the pore-forming agent powder are mixed in a mass ratio of 6:4, a dispersant, a plasticizer and a binder are added to prepare an electrode side skeleton casting slurry, and an appropriate amount of zirconium oxide ball milling beads are added for ball milling for 36 hours to ensure mixing uniformity. 0.7 Ce 0.2 Y 0.1 O 3-δ The powder is used to prepare the electrolyte casting slurry, and the electrode and electrolyte slurry are used to prepare the electrode and electrolyte casting membrane using a membrane belt casting machine. The three layers of casting membrane are stacked according to the electrode casting membrane|electrolyte casting membrane|electrode casting membrane, and then multi-step hot pressing is performed at 85°C and 60Mpa pressure. After sintering, an integrated "porous layer|dense layer|porous layer" structural skeleton with proton conduction is obtained, and the sintering temperature is kept at 1400°C for 10 hours. The porosity of the prepared BZCY conductor skeleton is 70%, and the average pore size is 98μm.

[0082] S2: preparing a protective layer on the surface of the proton conductor skeleton.

[0083] GDC powder (molar composition of 40% Gd2O3 stabilized CeO2) was dissolved in an ethanol solution, and appropriate amounts of dispersants and surfactants were added to prepare a GDC impregnation solution with a concentration of 3 mol / L. The impregnation solution was dripped into the BZCY conductor skeleton, and placed in a muffle furnace for heat preservation at high temperature. The above operation was repeated many times until the solution could no longer penetrate, and then the temperature was kept at 1500℃ for 10 hours, and then cooled to room temperature.

[0084] S3: preparing a catalyst layer on the surface of the protective layer.

[0085] According to the molar ratio of Pr:Ni:Co=2:1:1, metal nitrates Pr(NO3)3, Ni(NO3)3, and Co(NO3)2 were mixed, and then a surfactant was added at 10% of the total mass of the added Pr, Ni, and Co elements, and a certain amount of water was added to prepare a PNC oxygen electrode impregnation solution with a concentration of 0.7 mol / L.

[0086] The metal nitrate solutions were mixed according to the molar ratio of Ni:Sm:Ce=5:1:4, and then a surfactant was added according to 10% of the total mass of Ni, Sm, and Ce elements, and a certain amount of water was added to prepare a Ni / SDC fuel electrode impregnation solution with a concentration of 0.7 mol / L.

[0087] The above impregnation solution is absorbed and dripped into the electrode skeleton of the corresponding functional area respectively, and then placed in a muffle furnace for debinding treatment. The above operation is repeated many times until the solution can no longer penetrate, and finally a secondary sintering is performed to obtain a complete solid oxide battery. The secondary sintering process is: keep warm at 1100°C for 20 hours, and finally cool to room temperature.

[0088] The prepared solid oxide battery protection layer completely covers the proton conductor skeleton, the prepared gradient layer has a thickness of 4.5 μm, and the gradient layer is a Y and Ba intermediate phase.

[0089] The prepared solid oxide battery operated at 500°C for 1000 h without any power density decay.

[0090] Example 4

[0091] An embodiment of the present invention provides a method for preparing a solid oxide battery, and a solid oxide battery prepared by the method, the method comprising:

[0092] S1 prepares the proton conductor skeleton of the functional layer.

[0093] Using BaZr 0.7 Ce 0.2 Y 0.1 O 3-δ As an integrated proton conductor skeleton, specifically, the powder and the pore-forming agent powder are mixed in a mass ratio of 6:4, a dispersant, a plasticizer and a binder are added to prepare an electrode side skeleton casting slurry, and an appropriate amount of zirconium oxide ball milling beads are added for ball milling for 36 hours to ensure mixing uniformity. 0.7 Ce 0.2 Y 0.1 O 3-δ The powder is used to prepare the electrolyte casting slurry, and the electrode and electrolyte slurry are used to prepare the electrode and electrolyte casting membrane using a membrane belt casting machine. The three layers of casting membrane are stacked according to the electrode casting membrane|electrolyte casting membrane|electrode casting membrane, and then multi-step hot pressing is performed at 85°C and 60Mpa pressure. After sintering, an integrated "porous layer|dense layer|porous layer" structural skeleton with proton conduction is obtained, and the sintering temperature is kept at 1400°C for 10 hours. The porosity of the prepared BZCY conductor skeleton is 70%, and the average pore size is 98μm.

[0094] S2: preparing a protective layer on the surface of the proton conductor skeleton.

[0095] LDC(Ce 0.6 La 0.4 O2) powder was dissolved in ethanol solution, and appropriate amount of dispersant and surfactant were added to prepare LDC impregnation solution with concentration of 3 mol / L. The impregnation solution was dripped into the BZCY conductor skeleton, and placed in a muffle furnace for heat preservation at high temperature. The above operation was repeated many times until the solution could not penetrate, and then kept at 1450℃ for 10 hours, and then cooled to room temperature.

[0096] S3: preparing a catalyst layer on the surface of the protective layer.

[0097] According to the molar ratio of Pr:Ni:Co=2:1:1, metal nitrates Pr(NO3)3, Ni(NO3)3, and Co(NO3)2 were mixed, and then a surfactant was added at 10% of the total mass of the added Pr, Ni, and Co elements, and a certain amount of water was added to prepare a PNC oxygen electrode impregnation solution with a concentration of 0.7 mol / L.

[0098] The metal nitrate solutions were mixed according to the molar ratio of Ni:Sm:Ce=5:1:4, and then a surfactant was added according to 10% of the total mass of Ni, Sm, and Ce elements, and a certain amount of water was added to prepare a Ni / SDC fuel electrode impregnation solution with a concentration of 0.7 mol / L.

[0099] The above impregnation solution is absorbed and dripped into the electrode skeleton of the corresponding functional area respectively, and then placed in a muffle furnace for debinding treatment. The above operation is repeated many times until the solution can no longer penetrate, and finally a secondary sintering is performed to obtain a complete solid oxide battery. The secondary sintering process is: keep warm at 1100°C for 20 hours, and finally cool to room temperature.

[0100] The prepared solid oxide battery protection layer completely covers the proton conductor skeleton, the prepared gradient layer has a thickness of 4.4 μm, and the gradient layer is a Y and Ba intermediate phase.

[0101] The prepared solid oxide battery operated at 500°C for 1000 h without any power density decay.

[0102] Example 5

[0103] An embodiment of the present invention provides a method for preparing a solid oxide battery, and a solid oxide battery prepared by the method, the method comprising:

[0104] S1 prepares the proton conductor skeleton of the functional layer.

[0105] Using BaZr 0.7 Ce 0.2 Y 0.1 O 3-δ As an integrated proton conductor skeleton, specifically, the powder and the pore-forming agent powder are mixed in a mass ratio of 6:4, a dispersant, a plasticizer and a binder are added to prepare an electrode side skeleton casting slurry, and an appropriate amount of zirconium oxide ball milling beads are added for ball milling for 36 hours to ensure mixing uniformity. 0.7 Ce 0.2 Y 0.1 O 3-δThe powder is used to prepare the electrolyte casting slurry, and the electrode and electrolyte slurry are used to prepare the electrode and electrolyte casting membrane using a membrane belt casting machine. The three layers of casting membrane are stacked according to the electrode casting membrane|electrolyte casting membrane|electrode casting membrane, and then multi-step hot pressing is performed at 85°C and 60Mpa pressure. After sintering, an integrated "porous layer|dense layer|porous layer" structural skeleton with proton conduction is obtained, and the sintering temperature is kept at 1400°C for 10 hours. The porosity of the prepared BZCY conductor skeleton is 70%, and the average pore size is 98μm.

[0106] S2: preparing a protective layer on the surface of the proton conductor skeleton.

[0107] SDC(Sm 0.2 Ce 0.8 O 2) The powder was dissolved in an ethanol solution, and an appropriate amount of dispersant and surfactant were added to prepare an LDC impregnation solution with a concentration of 3 mol / L. The impregnation solution was dripped into the BZCY conductor skeleton, and placed in a muffle furnace for heat preservation at high temperature. The above operation was repeated many times until the solution could not penetrate, and then kept at 1450℃ for 10 hours, and then cooled to room temperature.

[0108] S3: preparing a catalyst layer on the surface of the protective layer.

[0109] According to the molar ratio of Pr:Ni:Co=2:1:1, metal nitrates Pr(NO3)3, Ni(NO3)3, and Co(NO3)2 were mixed, and then a surfactant was added at 10% of the total mass of the added Pr, Ni, and Co elements, and a certain amount of water was added to prepare a PNC oxygen electrode impregnation solution with a concentration of 0.7 mol / L.

[0110] The metal nitrate solutions were mixed according to the molar ratio of Ni:Sm:Ce=5:1:4, and then a surfactant was added according to 10% of the total mass of Ni, Sm, and Ce elements, and a certain amount of water was added to prepare a Ni / SDC fuel electrode impregnation solution with a concentration of 0.7 mol / L.

[0111] The above impregnation solution is absorbed and dripped into the electrode skeleton of the corresponding functional area respectively, and then placed in a muffle furnace for debinding treatment. The above operation is repeated many times until the solution can no longer penetrate, and finally a secondary sintering is performed to obtain a complete solid oxide battery. The secondary sintering process is: keep warm at 1100°C for 20 hours, and finally cool to room temperature.

[0112] The prepared solid oxide battery protection layer completely covers the proton conductor skeleton, the prepared gradient layer has a thickness of 4.3 μm, and the gradient layer is a Y and Ba intermediate phase.

[0113] The prepared solid oxide battery operated at 500°C for 1000 h without any power density decay.

[0114] Comparative Example 1

[0115] Compared with Example 1, in step S2 of this comparative example, the temperature is kept at 1100° C. for 3 hours and then cooled to room temperature.

[0116] The thickness of the prepared solid oxide battery gradient layer is 0.7 μm, and the power density of the solid oxide battery decays by 10% after operating at 400°C for 1000 hours.

[0117] Comparative Example 2

[0118] Compared with Comparative Example 3, in step S2 of this comparative example, the temperature is kept at 1500° C. for 12 h and then cooled to room temperature.

[0119] The thickness of the prepared solid oxide battery gradient layer is 4.8 μm, and the power density of the solid oxide battery decays by 12% after operating at 500°C for 1000 hours.

[0120] Comparative Example 3

[0121] Compared with Example 1, in step S2 of this comparative example, a GDC impregnation solution having a concentration of 0.4 mol / L was prepared.

[0122] The thickness of the prepared solid oxide battery gradient layer is 0.8 μm, and the power density of the solid oxide battery decays by 5% after operating at 500° C. for 1000 h.

[0123] Comparative Example 4

[0124] Compared with Example 3, in step S2 of this comparative example, a GDC impregnation solution having a concentration of 3.2 mol / L was prepared.

[0125] The thickness of the prepared solid oxide battery gradient layer is 4.7 μm. The solid oxide battery operates at 500° C. for 1000 h without any attenuation in power density, but the power density is reduced by 3% compared with Example 3.

[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A solid oxide battery containing a gradient layer, characterized in that: The functional layer of the solid oxide battery includes a proton conductor skeleton, a protective layer and a catalyst layer; The protective layer is attached to the surface of the proton conductor skeleton and includes a barrier layer and a gradient layer, and the gradient layer is generated by the reaction between the protective layer and the proton conductor skeleton nearby; The catalyst layer is attached to the barrier layer.

2. The solid oxide battery according to claim 1, characterized in that The thickness of the gradient layer in the solid oxide cell is 1.0-4.5 μm.

3. The solid oxide battery according to claim 1, characterized in that: The material of the proton conductor skeleton includes: BaZr 1-x Y x O 3-δ 、BaZr 1-x Yb x O 3-δ 、BaZr 1-x-y Ce y Y x O 3-δ 、BaZr 1-x-y-z Ce z Y y Yb x O 3-δ One or more of, where 0 <x<1,0<y<1,0<z<1,0<δ<1。 4. The solid oxide battery according to claim 1, characterized in that The materials of the protective layer include: CeO2, Ce 1-x G x O 2-δ 、Ce 1-x La x O 2-δ 、Sm 1-x Ce x O 2-δ One or more of, where 0 <x<1,0<y<1,0<δ<1。 5. The solid oxide battery according to claim 1, characterized in that: The porosity of the solid oxide battery functional layer is 10%-60%.

6. A method for preparing a solid oxide battery according to any one of claims 1 to 5, characterized in that: include: Prepare a proton conductor skeleton of a functional layer; Preparing a protective layer on the surface of the proton conductor skeleton; A catalyst layer is prepared on the surface of the protective layer.

7. The preparation method according to claim 6, characterized in that: Preparing a protective layer on the surface of the proton conductor skeleton comprises: Dissolving the material of the protective layer in an organic solvent and stirring to prepare an impregnation solution; The impregnation solution is dripped onto the proton conductor skeleton by an impregnation method, and then a heat preservation treatment is carried out at a first preset temperature. After the heat preservation is completed, the temperature is lowered and the impregnation process is repeated until the impregnation mass no longer increases, and then a sintering is carried out.

8. The preparation method according to claim 7, characterized in that: The particle size of the material powder of the protective layer is no more than 60 nm, and the concentration of the impregnation solution is 0.5-3.0 mol / L.

9. The preparation method according to claim 7, characterized in that: The first preset temperature is 300-500°C for 1-5h; The primary sintering process is: heating to 1100-1500° C. at a rate of no more than 5° C. / min, maintaining the temperature for 4-10 hours, and then cooling to room temperature.

10. The preparation method according to claim 6 or 9, characterized in that: Preparing a catalyst layer on the surface of the protective layer comprises: Catalyst material is prepared on the surface of the protective layer, and then secondary sintering is performed. The secondary sintering process is: heating to 600-1100° C. at a rate of no more than 3° C. / min, maintaining the temperature for 2-20 hours, and then cooling to room temperature.

Citation Information

Patent Citations

  • Thin solid oxide cell

    CA2669811A1

  • Solid oxide fuel cell composite cathode and preparation method thereof

    CN102683722A

  • Tourmaline lamella sintered on surface of honeycomb ceramic passage

    CN102718556A

  • Proton conductor low-temperature solid oxide cell with integrated components and preparation of proton conductor low-temperature solid oxide cell

    CN105762391A

  • Novel solid oxide fuel cell barrier layer and production method thereof

    CN106558716A